Somatic and Germinal Mobility of the RescueMu Transposon in Transgenic Maize - Raizada, Manish N. (American Society of Plant Biologists, 2001)
RescueMu, a Mu1 element containing a bacterial plasmid, is mobilized by MuDR in transgenic maize. Somatic excision from a cell-autonomous marker gene yields >90% single cell sectors; empty donor sites often have deletions and insertions, including up to 210 bp of RescueMu/Mu1 terminal DNA. Late somatic insertions are contemporaneous with excisions, suggesting that “cut-and-paste” transposition occurs in the soma. During reproduction, RescueMu transposes infrequently from the initial transgene array, but once transposed, RescueMu is suitable for high throughput gene mutation and cloning. As with MuDR/Mu elements, heritable RescueMu insertions are not associated with excisions. Both somatic and germinal RescueMu insertions occur preferentially into genes and gene-like sequences, but they exhibit weak target site preferences. New insights into Mu behaviors are discussed with reference to two models proposed to explain the alternative outcomes of somatic and germinal events: a switch from somatic cut-and-paste to germinal replicative transposition or to host-mediated gap repair from sister chromatids.